MENINGKATKAN HASIL BELAJAR IPA SISWA MELALUI MODEL PEMBELAJARAN INSIDE OUTSIDE CIRCLE DI KELAS IV SD NEGERI 020620 BINJAI SELATAN - Khairul Anwar (JURNAL HANDAYANI PGSD FIP UNIMED, 2017)
Abstract: Improving Student Learning Outcomes Through Learning Model Inside Outside Circle In Grade IV SD Negeri 020620 South Binjai. The purpose of research to improve student learning outcomes on the subjects of natural science. The subjects of this study were students of class IV of 20 students consisting of 10 men and 10 women. The result of the research on cycle I of classical completeness level is that there are 4 students (20%), and 16 students (80%) with an average grade of 54.75. Observation data of teacher teaching activity in cycle I meeting I (50,00) and meeting II (71,87). Student learning activity in cycle I meeting I (40,62) and meeting II (62,50). Cycle II there are 17 students (85%), and 3 students (15%) with an average score of 84.75. Observation data of teacher teaching activity in cycle II of meeting I (84,37) and meeting II (93,75). Student learning activity in cycle II of meeting I (71,87) and meeting II (90,62) Keywords:  IOC Model, Science Learning Outcomes. Abstrak: Meningkatkan Hasil Belajar IPA Siswa Melalui Model Pembelajaran Inside Outside Circle Di Kelas IV SD Negeri 020620 Binjai Selatan. Tujuan penelitian untuk meningkatkan hasil belajar siswa pada mata pelajaran ilmu pengetahuan alam. Subyek penelitian ini adalah siswa kelas IV sebanyak 20 orang siswa terdiri dari 10 laki-laki dan 10 perempuan. Hasil penelitian pada siklus I tingkat ketuntasan klasikal yaitu terdapat 4 orang siswa (20%), dan 16 orang siswa (80%) dengan nilai rata-rata 54,75. Data observasi aktivitas mengajar guru pada siklus I pertemuan I (50,00) dan pertemuan II (71,87). Aktivitas belajar siswa pada siklus I pertemuan I (40,62) dan pertemuan II (62,50). Siklus II terdapat 17 orang siswa (85%), dan 3 orang siswa (15%) dengan nilai rata rata 84,75. Data observasi aktivitas mengajar guru pada siklus II pertemuan I (84,37) dan pertemuan II (93,75). Aktivitas belajar siswa pada siklus II pertemuan I (71,87) dan pertemuan II (90,62)  Kata Kunci: Model IOC, Hasil Belajar IPA